Parametric Programming Applied to the Optimal Production Structure in Determining - Nagy, Lajos; Csipkés, Margit (International Journal of Engineering and Management Sciences, 2017)
The agricultural planning often the question arises, how the different input (fertilizer, feed, irrigation, etc) from what to use on a production (land, animals) unit basis, and to what intensity. The input transformational efficiency experiments by setting analysis and evaluation. For example examined the nutrient replenishers fertilization experiments, the effect of nutritional values of the feed on the body weight gain, milk production in animal experiments. The input input efficiency to the external environment (weather, soil conditions, unexpected events), the technology used and the biological factors both influence. The farmer must be chosen in each sector, taking into account the magnitude of these inputs and environmental requirements. The economic optimum is usually trying to approach the sectoral level, which serves as the basis for future planning data. The mathematical programming models using relatively simply and quickly determine the optimal production structure. The models provide the specific resource requirements for, and the limitations of the objective function coefficients are calculated on the basis of sectoral. This becomes a deterministic model, and we can get the appropriate sectoral analyzes outstanding results of production structures. Therefore the relationships within sectors directly incorporate mathematical programming model and corporate interests placed above the interests of the industry to determine the intensity of the sectoral inputs. in their article a fertiliser application example, we present the production structure and the plant production sector fertiliser input of a time optimization, in which the fertilizer for specified sectoral relationships appear in the model objective function.